Crown dimensions and proximal enamel thickness of mandibular second bicuspids - Sérgio Augusto Fernandes; Flávio Vellini-Ferreira; Helio Scavone-Junior; Rívea Inês Ferreira (Sociedade Brasileira de Pesquisa Odontológica, 2011)
To achieve proper recontouring of anterior and posterior teeth, to obtain optimal morphology during enamel stripping, it is important to be aware of dental anatomy. This study aimed at evaluating crown dimensions and proximal enamel thickness in a sample of 40 extracted sound, human, mandibular, second bicuspids (20 right and 20 left). Mesiodistal, cervico-occlusal and buccolingual crown dimensions were measured using a digital caliper, accurate to 0.01 mm. Teeth were embedded in acrylic resin and cut along their long axes through the proximal surfaces to obtain 0.7 mm-thick central sections. Enamel thickness on the cut sections was measured using a perfilometer. Comparative analyses were carried out using the Student's-t test (α= 5%). The mean mesiodistal crown widths for right and left teeth were 7.79 mm (± 0.47) and 7.70 mm (± 0.51), respectively. Mean cervico-occlusal heights ranged from 8.31 mm (± 0.75) on the right to 8.38 mm (± 0.85) on the left teeth. The mean values for the buccolingual dimension were 8.67 mm (± 0.70) on the right and 8.65 mm (± 0.54) on the left teeth. The mean enamel thickness on the mesial surfaces ranged from 1.35 mm (± 0.22) to 1.40 mm (± 0.17), on the left and right sides, respectively. On the distal surfaces, the corresponding values were 1.44 mm (± 0.21) and 1.46 mm (± 0.12). No significant differences were found between measurements for right and left teeth. However, enamel thickness was significantly greater on the distal surfaces, compared with the mesial surfaces.